Penetrating eye injuries from writing instruments - Kelly, Simon P (Dove Medical Press, 2012)
PURPOSE: To consider the potential for ocular injury from writing implements by presenting four such cases, and to consider the incidence of such eye injuries from analysis of a national trauma database. METHODS: The Home and Leisure Accident Surveillance System was searched for records of eye injuries from writing instruments to provide UK estimates of such injuries. Four patients with ocular penetrating injury from pens or pencils (especially when caused by children), and examined by the authors, are described which illustrate mechanisms of injury. RESULTS: It is estimated that around 748 ocular pen injuries and 892 ocular pencil injuries of undetermined severity occurred annually in the UK during the database surveillance period 2000–2002. No eye injuries from swords, including toy swords and fencing foils, were reported. CONCLUSION: Ocular perforation sometimes occur from writing instruments that are thrown in the community, especially by children. Implications for policy and prevention are discussed. Non-specialists should have a low threshold for referring patients with eye injuries if suspicious of ocular penetration, even where caused by everyday objects, such as writing instruments.